Menyelidiki Persepsi Atlet, Peran Orang Tua, dan Pelatih Tentang Tingkat Motivasi Latihan Renang di Masa Pandemi Covid-19 - Gani, Ruslan Abdul; Setiawan, Edi; Mahardhika, Dhika Bayu; Syamsudar, Bangbang (Jurnal Porkes, 2022)
Motivation in the era of the Covid-19 pandemic is a very important element in maintaining the physical condition of athletes in training, with high motivation, the achievements of swimming athletes will obtain far more optimal performance results. This study aims to determine the perceptions of athletes, parents and coaches regarding exercise motivation during the Covid-19 pandemic. Motivation in the era of the Covid-19 pandemic is a very important element in maintaining the physical condition of athletes in training, with high motivation, the achievements of swimming athletes will obtain far more optimal performance results. This study aims to determine the perceptions of athletes, parents and coaches regarding exercise motivation during the Covid-19 pandemic. The population in this study were swimming athletes, parents and swimming coaches, the sample selection using purposive sampling technique. The motivational instrument used is in the form of a questionnaire conducted through interviews with the research sample. The results of the study showed that athletes and coaches had a high desire and motivation in training, but the parents did not give permission, because they were worried about the safety of their children practicing swimming which could allow them to be exposed to the Covid-19 virus. Thus, the athlete's motivation in participating in training is included in the high category and this condition must be maintained in order to get the optimal target.